Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Guru terhadap Kinerja dan Lingkungan Kerja - Barbara Green Winslet Bessie; Hendrik A. E. Lao (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the factors that influence teacher satisfaction with performance and work environment, essential for the quality of education. Through literature study, it was found that teacher satisfaction directly impacts performance (quality, quantity, punctuality of teaching). The work environment, both physical (school facilities) and non-physical (relationships between colleagues, management support, school climate), is a major determinant of satisfaction. Although teachers face challenges, a positive environment has been shown to increase satisfaction. It is concluded that satisfaction, performance, and work environment are mutually reinforcing. Strategic investment in these elements is essential to create a better education ecosystem.